Quality of doctor–patient relationship in patients with high somatic symptom severity in China. Issue 1 (February 2015) - Wu, Heng; Zhao, Xudong; Fritzsche, Kurt; Leonhart, Rainer; Schaefert, Rainer; Sun, Xiayuan; Larisch, Astrid
Highlights Patients with high SSS were rated as significantly more difficult by the doctors. Patients in TCM rated the quality of DPR significantly higher. Satisfaction of treatment and time of treatment were strong correlates for DPR. Other departments should learn from TCM to manage patients with high SSS.